The Sanghyang Dance : from its prehistoric origin to conservation effort - Alit Sankara (Bali Tourism Journal, 2020)
As a part of the sacred Wali dance, Sanghyang dance loaded with prehistoric spiritual values intended for worship on religious occasions. The sanghyang dance was well-known in most parts of the island. however, it has well-developed in several areas such as in Bangli, Gianyar, Karangasem, Buleleng, Jembrana, Tabanan, and Klungkung. The art’s existence showed that the Balinese people believe that spirit can help human life. There are commonly three important elements in typical sanghyang dance, namely Nusdus (medium purification), Gending Sanghyang (the melody) and the medium (people or dolls). The Sanghyang Dedari Sacred Dance at Geriana Kauh is the only Sanghyang dance routinely performed yearly. UNESCO recognized The Sanghyang Dedari sacred dance as an almost extinct world cultural heritage. However, the Sanghyang Dedari dance is only held once a year, with a long ritual preparation. A researcher from Indonesia University, Saraswati Putri took a long journey to reconstruct the indigenous dance. She interviewed many traditional village heads, checked Balinese manuscripts in Leiden, and then arranged them into Old Balinese or Sanskrit. Reconstructing from zero, connecting the scattered mosaic requires tenacity and determination. As a result of the hard work, The Sanghyang Dedari Giri Amertha Museum was built to preserve this dance